Unearthing The Psycho-Spiritual Values Within The Training Module for Disaster Workers - Othman, Khatijah; Nik Nazli, Nik Nadian Nisa; Mahyuddin, Muhammad Khairi; Sulaiman, Mashitah; Md. Hamdani, Suhailiza; Ahmad, Yuseri; Abdul Mutalib, Marina Munira; Mohd Sukor, Nurhafizah; Hamzah, Zulfadhli; Jusoh, Nor Adila Syahira (‘Abqari Journal, 2020)
Generally, the training module for disaster workers has been built based on technical skills as to affirm that the disaster workers capable of responding to any situation that occurs. However, in particular situation the psycho-spirituality skill is needed to deal with an unexpected scenario. The importance to understand the value of psycho-spirituality is vital, especially to the trainer of the disaster module. This study has been conducted to the trainers of one of the disaster agencies in Malaysia. The interview has been conducted to six trainers whereby nine structured questions regarding the necessary skills taught to the disaster workers and the needs of psycho-spirituality skills to respond during the disaster. The finding shows that the trainers have a consensus agreement that the technical skills form as prior knowledge for the disaster workers. By having the psycho spiritual content in the training module, they can balance their emotional, internal spiritual and physical well-being while maintaining resilient. Thus, this study suggests that psycho-spiritual content is very much important to be included in the training module for disaster workers as to enhance the training content comprehensively both in technical and spiritual aspects.